Ethics of care and health policy change: Indian women's movement mobilizes against quinacrine sterilization - Visvanathan, Nalini (1999)
Nalini Visvanathan looks at how the campaign around banning quinacrine in India shows the importance of ethics of care over utilitarian approaches to women's reproductive health. - Reproduced
Keywords: Health services